Policy interventions, market, and trade considerations with special reference to rapeseed and mustard: POLICY INTERVENTIONS, MARKET, AND TRADE CONSIDERATIONS TO RAPESEED AND MUSTARD - ANUPAM BARIK (Journal of Oilseeds Research, 2023)
Rapeseed and mustard oil is one of the most consumed edible oils in India due to pungency and colour. India needs nearly 15-20 million tonnes of rapeseed and mustard seed to meet its growing demand as against current production of 9-10 million tonnes of seeds. As per WHO standards, mustard oil with low saturated fatty acid content and high mono unsaturated fatty acid content is a healthy oil and therefore needs special importance in domestic edible oil basket. Currently (2022-23), Government of India (GOI) is implementing National Food Security Mission (NFSM) - (Oilseeds & Oil palm) for increasing oilseeds production and area expansion under oil palm. The NFSM (OS&OP) will be dropped and two new Scheme National Mission on Edible oils (NMEO)-Oilseeds and NMEO-Oil Palm will be implemented with the aim to enhance the edible oilseeds production and oils availabilityin the countrybyharnessing oilseeds and palmoil productivityand to reduce import burden on edible oils. Besides, NMEO-OS the private participation in technology demonstration, input supply, procurement of produce, value addition, infrastructure development and honey production are very much essential to increase edible oils production.